From the Absorptive Capacity of Middle Managers and Their Employees to the Commitment in the Implementation of New Work Routines - Chevrette, Nancie; Jean, Eric (American Journal of Management, 2023)
The objective of this proposal is to present a theoretical reflection on the concept of projects absorptive (absorption) capacity and the role of managers’ and employees’ commitment in the implementation of work routines. The general problem lies in a context of simultaneous project implementation, which can create additional pressure on employees with regard to available resources. The development of a theoretical framework, highlighting project implementation demands, absorptive capacity, routines and commitment, thus leads to the proposal of a three stage conceptual framework. The first moment represents the project during its implementation. The second moment specifically concerns absorptive capacity as a resource and the final moment highlights the relationship between absorptive capacity and commitment. Ultimately, this theoretical approach attempts to demonstrate that examining the project’s absorptive capacity reveals a significant theoretical originality, and that digging deeper into the concepts of commitment and work routines pushes the limits of project management research.